The Eastward Enlargement of the Eurozone : The Shaping of Capital Markets Regional Inputs on Data and Statistic - Thomas Meyer; Jaakko Kiander; Carlos Vieira; Isabel Vieira; Vladimir Lavrač; Massimiliano Marzo (Free University Berlin, Jean Monnet Centre of Excellence, 2002)
This paper has been prepared as a part of a broader Ezoneplus project that evaluates European Monetary Union (EMU) and its enlargement to prospective members in central and eastern Europe. The project is financially supported by European Commission (HPSE-CT-2001-00084). It contains the following chapters: I. Regional input: Capital markets in Benelux, France, and Germany II. Regional Input: Capital Markets in Portugal and Spain III. Regional Input: Capital Markets in Slovenia and Hungary IV. Capital Market Deregulation, Financial Integration and Macroeconomic Performance in the Nordic Countries in the 1980s: And there any Lessons? V. The Evolution of the Banking Industry in Italy and Austria after the Introduction of the Euro
Keywords: 330; Capital Markets; Transition Economies; EMU; EU-Erweiterung; Europäische Wirtschafts- und Währungsunion; Internationaler Finanzmarkt; Marktintegration; EU-Staaten; Osteuropa